1973
DOI: 10.1677/joe.0.0590217
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Food, Gastro-Intestinal Hormones and Calcitonin Secretion

Abstract: The role of calcitonin (CT) in postprandial calcium homeostasis and the possibility of a gastroentero-thyroid C-cell system was studied in young pigs. When pigs were fasted for more than 36 h and then fed, the plasma calcium concentration decreased by 6\m=.\1 % over a period of 60\p=n-\120 min after a meal. Since in thyroidectomized pigs the plasma calcium concentration increased by 7\m=.\2 % when they were fed after a fast of 36 h it is suggested that increased CT secretion assists in the control of postprand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1975
1975
1996
1996

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 17 publications
(23 reference statements)
0
16
0
Order By: Relevance
“…Certain gastrointestinal hormones have been suspected of being secretagogues of calcitonin in man. Our own previously re ported in vitro studies with normal human thyroid tissue have demonstrated that gastrin stimulates the release of calcitonin [12], In addition, animal studies have demonstrated that gastrin also provokes the release of calci tonin in vivo [13]. In the study of Cooper et al [14] , calcitonin and gastrin were positively cor related in pig thyroid venous blood in the basal state as well as during stimulation by intragastric or intravenous calcium and intragastric acetylcholine.…”
Section: Discussionmentioning
confidence: 91%
“…Certain gastrointestinal hormones have been suspected of being secretagogues of calcitonin in man. Our own previously re ported in vitro studies with normal human thyroid tissue have demonstrated that gastrin stimulates the release of calcitonin [12], In addition, animal studies have demonstrated that gastrin also provokes the release of calci tonin in vivo [13]. In the study of Cooper et al [14] , calcitonin and gastrin were positively cor related in pig thyroid venous blood in the basal state as well as during stimulation by intragastric or intravenous calcium and intragastric acetylcholine.…”
Section: Discussionmentioning
confidence: 91%
“…Three different forms of GLP-1 are produced by intestinal L cells, GLP-1 (1 37), GLP-1 (7 36 amide), and GLP-1 (7-37), but only truncated forms of GLP-I are biologically active [4] as potent insulin secretagogues. The existence of a gastroentero-thyroidal axis involved in the control of calcitonin (CT) secretion was postulated 23 years ago [5]. Glucagon [6] as well as partially purified enteroglucagon were shown to stimulate the CT secretion rate in pigs [5].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of a gastroentero-thyroidal axis involved in the control of calcitonin (CT) secretion was postulated 23 years ago [5]. Glucagon [6] as well as partially purified enteroglucagon were shown to stimulate the CT secretion rate in pigs [5]. We have therefore studied the effects of GLP-1 (7-37) on the secretion of CGRP and CT by the CA-77 C cell line, and on the steady-state level of their mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…One hour after administration of soybean oil by force-feeding, the plasma CT level was significantly increased in the 2-hour old newborn rat (Garel and Jullienne, 1977). In a 30-kg pig, the administration of intraduodenal fat was shown to stimulate CT secretion 1 h later (Swaminathan et al, 1973). However, gastric distension alone is capable of stimulating not only gastrin secretion but also CT secretion (Swaminathan et al, 1973).…”
mentioning
confidence: 99%
“…In a 30-kg pig, the administration of intraduodenal fat was shown to stimulate CT secretion 1 h later (Swaminathan et al, 1973). However, gastric distension alone is capable of stimulating not only gastrin secretion but also CT secretion (Swaminathan et al, 1973). In 2-hour old fasted newborn rats, gastric distension remained without effect on CT secretion since force-feeding 0.9 p. 100 NaCI in control animals did not change the plasma CT concentration (Garel and Jullienne, 1977 (Garel and Jullienne, 1977).…”
mentioning
confidence: 99%